THE ADVANCEMENT OF ZAKAT INSTITUTION IN MALAYSIAN POST ISLAMIC REVIVALISM ERA - Sarif, Suhaili; Ali, Nor Aini; Kamri, Nor ’Azzah (Journal of Al-Tamaddun, 2020)
Zakat is an important Islamic institution in Malaysia. The development of the institution has been through time influenced by the changing social, political and economic situation of the country. One of the important phenomena that shaped the institution is the Islamization process which happened during Islamic revivalism which ushered in the early 1970s. The scenario and the social change that happened during the era have resulted in the zakat has been one of the institutions which government keened to enhance in the later decades. This article discusses the brief development of zakat institution in post Malaysian Islamic revivalism era, through which eventually, the impact of the revivalism on the institution will be clearly observed. As has been self-evident throughout the discussion, supported by the data of collection over the years, the zakat institution, apart from its fundamental role as religious duty, has been through time playing a greater role in social and economy.